Novel milk-based oral formulations: Proof of concept - Charkoftaki, Georgia; Kytariolos, John; Macheras, Panos (INTERNATIONAL JOURNAL OF PHARMACEUTICS, 2010)
The aim of this study is to develop milk-based formulations for ionized and unionized lipophilic drugs. Solubility studies of the following non-steroidal anti-inflammatory drugs (NSAIDs): mefenamic acid, tolfenamic acid, ketoprofen, meloxicam, tenoxicam and nimesulide in phosphate- and glycine-NaOH buffers at nominal pH 8-12. were performed. The solubilities of cyclosporine and danazol in water-ethanol solutions were studied. NSAIDs-, cyclosporine-, danazol-, aspirin-milk oral liquid formulations were prepared by adding the appropriate volume of (i) NSAIDs-alkaline buffer solutions, (ii) water-ethanol solutions of cyclosporine and danazol and (iii) aspirin aqueous solution to 150-200 ml of milk. All the non-steroidal anti-inflammatory drugs exhibited increased solubility in the alkaline buffers. The actual pH values (range 6.7-7.7) of the final NSAIDs-milk formulations were very close to milk pH. The higher ethanol content in ethanol-water mixtures increased the solubility of danazol and cyclosporine. A 15 mg meloxicam-, a 100 mg cyclosporine- and a 500 mg aspirin-milk formulation was administered orally to healthy volunteers. All these formulations showed a satisfactory in vivo performance. The strong buffering capacity of milk that was observed and the high solubility of unionized drugs in ethanol allow the preparation of drug-milk formulations with enhanced pharmacokinetic properties. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Aspirin; Cyclosporine; Danazol; milk; NSAIDs; Oral formulations